Key Issues in the Intellectual Property Court's Presidium Rulings - Kolzdorf, Maria; Kapyrina, Natalia; Goloiad, Nikolai (Legal Issues in the Digital Age, 2024)
The authors review key positions in the rulings of the Presidium of the Russian Intellectual Property Court (IPC) issued between October and December of 2023. The Chamber hears cassation appeals against the decisions of the IPC first instance and deals primarily, but not only, with matters of registration and validity of industrial property rights. Therefore, the review predominantly covers substantive requirements for patent and trademark protection, as well as procedural issues both in the administrative adjudicating mechanism at the Patent Office (Rospatent) and at the IPC itself. Apart of it, the current review encompasses a variety of aspects related to trademark law and to various procedural matters covering activities of the Rospatent and the Intellectual Property Court.